'Luring the infant into life' : exploring infant mortality and infant-feeding in Khayelitsha, Cape Town - Majombozi, Ziyanda (Social Anthropology, 2016)
The ethnographic data presented in this dissertation is drawn from 20 weeks of informal interviews, participant observation, and other creative research methods such as the use of social media platforms like Facebook and WhatsApp, WhatsApp interviews, focus groups and pictures. Drawing on concepts of managing risk, this dissertation demonstrates that in a world where life is precarious due to illnesses, poverty and other social ills that reflect the political economy of the different spaces, child care is about sustaining the life of an infant. This paper explores the different ways that the state (represented through the National Department of Health) and mothers imagine themselves to be sustaining infant life. It further explores the complexities that arise when the state, external health institutions as well as the mother together with her family and friends imagine the process of sustaining infant life differently. This paper argues that infant feeding choices reflect the different discourses that surround 'sustaining life' and 'managing risk'. It aims to show that the introduction of exclusive breastfeeding policies is a manifestation of the state's ideas on how to sustain infant life. In contrast, the introduction of medicine and complimentary feeds reflect the ideas mothers have for sustaining the lives of their infants. This paper suggests that, although exclusive breastfeeding is important, there are different ways to sustain infant life that are not within the biomedical framework. Alas, these are often dismissed as barriers to exclusive breastfeeding and isolated from other tools used to sustain infant life and to address infant mortality.